MAJELIS TA'LIM AS SOCIALIZATION MEDIA OF CHILD PROTECTION IN WEST SULAWESI - Abdul Rahman; Anwar Sadat (Al-Qalam, 2021)
The enactment of Law No. 35 of 2014 concerning Child Protection is intended to protect children and guarantee their rights to live, grow, develop, and participate optimally following human dignity and get protection from violence and discrimination. It could be achieved through increasing awareness of the rights and obligations and the responsibility of the involved parties, especially parents because they are the first and foremost in contact with children. In the context of the Law socialization, research is needed to find an appropriate and effective socialization model especially for women (mothers) through religious-social activities. One of them is majelis ta'lim program. This research used a normative-empirical research type. Normative research was used through the interpretation of grammatical and authentic legal methods. Empirical research was conducted by a teleological interpretation method to know the extent of the legal norm according to the community’s attitudes, behaviors, and compliance. Data were collected through the study of literature and empirical studies using interview guidelines and questionnaires. The research results showed that the developed socialization model could solve the most fundamental and urgent literature and the wider community’s interests. In protecting the community-based program, the issue is not merely children in conflict with the law. It includes a larger unit of interaction, such as parents, family, peers, environment, and wider social institutions